Pendampingan Pengelolaan Inovasi, Peluang, dan Tantangan Usaha di Bidang Kesehatan - Nudji, Bambang; Sutha, Diah Wijayanti (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Community service activities aim to improve the capacity of students in the health sector in entrepreneurship. . The Community-Based Research (CBR) method is used to encourage active student participation, identify needs, and develop community-based solutions. During the activity, participants participated in socialization sessions, interactive discussions, and business idea development workshops. The results of the activities showed an increase in students' understanding and confidence in facing the challenges of entrepreneurship in the health sector. In addition, several student groups are committed to continuing the development of business ideas with support from the incubation program that will be provided by the institution. community